Lysine–arginine advanced glycation end‐product cross‐links and the effect on collagen structure: A molecular dynamics study. Issue 5 (23rd December 2020) - Nash, Anthony; Noh, Sang Young; Birch, Helen L.; de Leeuw, Nora H.
Abstract: The accumulation of advanced glycation end‐products is a fundamental process that is central to age‐related decline in musculoskeletal tissues and locomotor system function and other collagen‐rich tissues. However, although computational studies of advanced glycation end‐product cross‐links could be immensely valuable, this area remains largely unexplored given the limited availability of structural parameters for the derivation of force fields for Molecular Dynamics simulations. In this article, we present the bonded force constants, atomic partial charges and geometry of the arginine‐lysine cross‐links DOGDIC, GODIC, and MODIC. We have performed in vacuo Molecular Dynamics simulations to validate their implementation against quantum mechanical frequency calculations. A DOGDIC advanced glycation end‐product cross‐link was then inserted into a model collagen fibril to explore structural changes of collagen and dynamics in interstitial water. Unlike our previous studies of glucosepane, our findings suggest that intra‐collagen DOGDIC cross‐links furthers intra‐collagen peptide hydrogen‐bonding and does not promote the diffusion of water through the collagen triple helices.